2022
DOI: 10.1186/s12916-022-02424-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined associations of family history and self-management with age at diagnosis and cardiometabolic risk in 86,931 patients with type 2 diabetes: Joint Asia Diabetes Evaluation (JADE) Register from 11 countries

Abstract: Background Family history (FamH) of type 2 diabetes might indicate shared genotypes, environments, and/or behaviors. We hypothesize that FamH interacts with unhealthy behaviors to increase the risk of early onset of diabetes and poor cardiometabolic control. Methods In a cross-sectional analysis of the prospective Joint Asia Diabetes Evaluation Register including patients from 427 clinics in 11 Asian countries/regions in 2007–2021, we defined posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In contrast, many previous studies have shown a negative association between family history and glycemic control [ 20 , 30 , 31 ]. However, Cheung et al reported similar findings to those of this study, with 86,931 patients from 11 Asian countries reporting lower HbA 1C among patients with a positive parental history as compared to those with a negative parental history [ 32 ].…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, many previous studies have shown a negative association between family history and glycemic control [ 20 , 30 , 31 ]. However, Cheung et al reported similar findings to those of this study, with 86,931 patients from 11 Asian countries reporting lower HbA 1C among patients with a positive parental history as compared to those with a negative parental history [ 32 ].…”
Section: Discussionsupporting
confidence: 84%
“…This can further inform individuals’ willingness and readiness to engage in preventative health behaviours—representing a valuable point of intervention (Table 2 ). Empirical studies have explored how having a family history of diseases such as T2D can interact with health behaviours to affect an individual’s cardiometabolic risk—highlighting the complex relationships between shared genotypes, environments and/or behaviours in informing disease risk [ 51 ]. Qualitative research also shows that participants often discuss risk as being “inherited” via lifestyle and habits from home, cultural or social environments [ 41 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other factors, including prenatal factors (e. g., low birth weight, maternal under-nutrition), the biological propensity to central obesity and insulin resistance, low lean mass, diabetes during pregnancy, impaired glucose tolerance, and urban stress are associated with a high prevalence of T2DM in Indian children and young adults. [1167][1168][1169][1170][1171][1172][1173][1174][1175] Data on the prevalence of young onset T2DM are scarce worldwide, especially in India 1176 . It has been estimated that 1 in 3 new cases of diabetes mellitus in the USA diagnosed in youth younger than 18 years is T2DM and is more common among youth between 10 and 19 years of age 1158 .…”
Section: Introductionmentioning
confidence: 99%